Penggunaan Bubuk Bentonite untuk Menjernihkan Solar dari Olahan Sampah Plastik dan Oli Bekas - Khoirunisa, Amanda; Tirtoardi, Yudo; Pratama, Ahmad Juang (Universitas Al Azhar Indonesia, 2024)
Plastic to Solar (PLATOS) machine is a machine that processes plastic waste or used oil into fuel through a pyrolysis process. Based on observations made, pure diesel produced by the PLATOS machine has a very cloudy color or brownish black. Therefore, to get clearer fluid, a purification process is needed, one of which is by using bentonite powder. Bentonite powder used is Bleaching Earth Bentonite which can bind or absorb dirt and unwanted materials in oil or diesel, so that oil or diesel becomes paler and clearer. The heating method is used in the purification trial using a blow torch fire flame gun and an aluminum pan as a diesel fuel container. This study aims to observe the extent of the effect of using bentonite to improve the quality of diesel fuel that has been produced. The research was conducted by conducting 4 times the purification process with the same amount of bentonite and diesel weight of 20 grams and 1 liter. Based on the experiments that have been carried out, it can be concluded that the diesel produced has specifications that are within the limits of diesel specifications set by the Director General of Oil and Gas. Overall, the results of these specifications can state that the use of bentonite powder with heating methods up to 100o C can improve the quality of diesel fuel well.Keywords – Bentonite, Purification Process, Pyrolysis, Solar.